Using the Web to Teach Library Research Skills in Introductory Biology: A Collaboration Between Faculty and Librarians - Colin Orians; Laurie Sabol (Issues in Science and Technology Librarianship)
Web-based instruction is an effective way, if used correctly, to teach students how to use library resources. In this article we describe a collaboration between the Department of Biology and the Library to develop such a web site for introductory biology. Our goals were to develop early in the students' careers library research skills, to show that such skills are necessary for effective scientific communication, and to provide students with varied backgrounds the skills to independently identify, locate, evaluate and use the library's resources. In addition to describing the site, we discuss ongoing changes to the web site and to the course that have improved its effectiveness. Student evaluations suggest we have met our goals, and colleagues have used the site as a foundation for the development of a more advanced site.